Effects of Drought and Temperature Stress on Germination and Seedling Development of Sunflower - Nurgül Ergin; Mehmet Demir Kaya (Turkish Journal of Agriculture: Food Science and Technology, 2020)
This study was aimed to determine the responses of some sunflower hybrids to drought and low temperature stresses during germination and seedling development period. Sunflower hybrids of Sanbro MR, 63LE113, 64LL62 and Meteor were used in the study. Germination percentage, mean germination time, root and shoot length, root / shoot ratio, seedling fresh and dry weight of the sunflower hybrids were investigated at two temperatures (low 15°C and optimum 25°C) and drought stresses (distilled water, -1.5, -3.0, -4.5 and -6.0 bar) induced by polyethylene glycol 6000. The results of the research showed that there were significant differences among the sunflower hybrids in terms of the investigated characteristics. Increased drought stresses led to decreasing germination percentage, root and shoot length, seedling fresh weight, but caused a prolonged germination time and increased seedling dry weight. No significant change was observed in the germination and seedling development of the sunflower up to drought of -3,0 bar. The root / shoot ratio of sunflower hybrids increased at 15°C. The Sanbro MR had the fastest and highest germination along with the highest seedling fresh and dry weight at low temperature and higher drought stresses. It was concluded that sunflower hybrid Sanbro MR gave better performance under drought and low temperature conditions than the other hybrids.